2008
DOI: 10.1080/19942060.2008.11015230
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flows of Droplets in Contractions and Double Bends

Abstract: Transient two-phase liquid-liquid flows of Newtonian fluid droplets in a primary Newtonian fluid with different viscosities, through constricted channels and double-bend channels, are numerically modelled and studied. The deformation and migration of various arrangements (arrays) of droplets, as they are carried by the primary phase into the low Reynolds number (Re), developing Hagen-Poiseuille laminar flow, is computed and discussed on the basis of the non-dimensional numbers: Capillary number (Ca), Reynolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…Taylor deformation factor: L : maximum length of the droplet/bubble during the deformation process; B : minimum length of the droplet/bubble during the deformation process. [25] L D L : maximum length of the droplet/bubble during the deformation process;…”
Section: L−b L+bmentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor deformation factor: L : maximum length of the droplet/bubble during the deformation process; B : minimum length of the droplet/bubble during the deformation process. [25] L D L : maximum length of the droplet/bubble during the deformation process;…”
Section: L−b L+bmentioning
confidence: 99%
“…Straight Droplet breakup [30] Tapered/ conical Droplet breakup [27] Sinusoidal/ cosine Oil trapping, droplet breakup [31] Double-bend Provides deformation and rotation [25] Saw-tooth-shaped Directional transportation by periodic half-open capillary channels [32] Hyperbolic channel Capsule dynamics, encapsulate droplet [33] Shark teeth Provides rapid deformation [34] Within constrictions, the number of possible arrangements is high, and Table 3 summarizes the main types of constrictions that are frequently reported in the literature. Table 3.…”
Section: Constriction Geometry Design Purpose Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent experimental studies of the flow inside real-size and large-scale model nozzles have revealed the complexity of the two-phase flow structures over different operating conditions (Soteriou et al, 1995;Chaves et al, 1995;Arcoumanis et al, 1999;Payri et al, 2007). The size of the injector nozzle and the high speed of fluid flow make it difficult to carry out experimental observations, so the use of numerical simulations (Bierbrauer and Zhu, 2008;Christafakis and Tsangaris, 2008) is very useful to understand the flow features inside and at the exit of the injector nozzle. Different numerical simulations have been reported focusing on cavitation inside the diesel engine injector.…”
Section: Introductionmentioning
confidence: 99%
“…Meacham et al (2005) quantified the formation and ejection of droplets using ultrasound while Amirzadeh and Chandra (2010) detailed the results of using a pneumatic droplet generator. Additional studies have been performed by Gjesing et al (2009) (Christafakis and Tsangaris, 2008). Due to the limited amount of research done on liquid droplet formation from ruptured tubes the aim of the current work is the development of an experimentally validated finite volume model that will simulate liquid droplet formation from a ruptured tube.…”
Section: Introductionmentioning
confidence: 99%